Dampak Norma Subyektif, Kompetensi Profesional terhadap Niat Whistleblowing di Lingkungan OPD Kabupaten Asahan dengan Reward Sebagai Faktor Moderasi - Raiesa Amin; Widia Astuti; Eka Nurmala Sari (Income Journal: Accounting, Management and Economic Research, 2024)
The aim of this research is to test and analyze the influence of subjective norms on whistleblowing intentions in the Asahan Regency OPD. To test and analyze the influence of professional competence on whistleblowing intentions in the Asahan Regency OPD. To test and analyze whether rewards can moderate the influence of subjective norms on whistleblowing intentions in the Asahan Regency OPD. To test and analyze whether rewards can moderate the influence of professional competence on whistleblowing intentions in the Asahan Regency OPD. This research uses associative research type. The population in this study was the OPD in Asahan Regency, totaling 28 OPD. The sampling technique in this research used random sampling type. So the number of samples used was 100 people. The data collection technique used in this research is the questionnaire method. The data analysis technique in this research uses Partial Least Square (PLS). The research results show that subjective norms influence whistleblowing intentions. The better the subjective norms available, the more the whistleblowing intention will increase. Professional competence influences whistleblowing intentions. The clearer the target of the audit report that is prepared, the better the whistleblowing intention. Rewards can moderate the influence of subjective norms on whistleblowing intentions. The higher the level of transparency, the better the level of whistleblowing intentions. Rewards can moderate the influence of professional competence on whistleblowing intentions. The higher the reward level, the better the level of whistleblowing intention.